Rotational stocking management on elephant grass for dairy cows: grazing strategies, animal productivity, enteric methane and nitrous oxide emissions - Congio, Guilhermo Francklin de Souza (2018)
Pasture-based systems are important milk suppliers to dairy industry and thereby will play relevant role to support the growing demand for food. However, this additional milk supply must be obtained through higher yields resulting from intensification of existing farming systems through strategies environmentally friendly and economically profitable towards sustainable intensification. The central hypothesis of this study was that simple grazing management strategies can improve the efficiency while reduce the key environmental issues of tropical pasture-based dairy systems. Two experiments were carried out on a rainfed and non-irrigated elephant grass (Pennisetum purpureum Schum. cv. Cameroon) pasture in Piracicaba, SP, Brazil. The objective of the first experiment was to investigate the influence of two pre-grazing targets (95% and maximum canopy light interception during pasture regrowth; LI95% and LIMAX, respectively) on sward structure and herbage nutritive value, dry matter intake (DMI), milk yield, stocking rate, enteric methane (CH4) emissions by Holstein × Jersey dairy cows, and nitrous oxide fluxes from the soil. Results indicated that pre-grazing canopy height was greater for LIMAX (≈135 cm) than LI95% (≈100 cm) and can be used as a reliable field guide for monitoring sward structure. Grazing management based on the LI95% target improved herbage nutritive value and grazing efficiency, allowing greater DMI, milk yield and stocking rate by dairy cows. Daily enteric CH4 emission was not affected; however, cows grazing elephant grass at LI95% were more efficient and emitted 21% less CH4/kg of milk yield and 18% less CH4/kg of DMI. The 51% increase in milk yield per hectare overcame the 29% increase in enteric CH4 emissions per hectare for the LI95% target. Nitrous oxide fluxes were not affected by pre-grazing targets. Overall, strategic grazing management is an environmentally friendly practice that improves the use efficiency of allocated resources through optimization of processes involving plant, ruminant and their interface, and enhances milk production efficiency of tropical pasture-based systems. Once the ideal pre-grazing target was established during he first experiment (LI95%), the second step consisted of a refinement of the first phase. The second objective was to describe and measure the influence of two timings of new paddock allocation to cows (AM and PM) on herbage chemical composition and DMI, milk yield, milk compostion, and enteric CH4 emissions of Holstein × Jersey dairy cows. Results supported the general understanding of diurnal variation in herbage chemical composition towards greater concentrations of dry matter and non-fibrous carbohydrates, and lower concentration of fiber components in the afternoon herbage. However, the higher nutritive value of the afternoon herbage did not result in increasead DMI and milk yield, or decreased intensity of CH4 emission by dairy cows. Our findings also indicate that new paddock allocation in the afternoon can be a simple and useful grazing strategy that results in greater N partitioning to protein yield, and lower excretion of urea N in milk. The association of LI95% pre-grazing target and PM allocation could bring economic, productive and environmental benefits towards sustainable intensification of tropical pasture-based systems.